VaKE and Education for Leadership and European Citizenship - Weyringer, Sieglinde; Patry, Jean- Luc (FAISCA. Revista de Altas Capacidades, 2007)
The article is meant to explicate the importance of problem solving in the classroom for student personal development, which is not being taught as a result of too much emphasis on content teaching. In order for skills to be taught to students, an idea of self is to develop in the student, a development which in itself prepares the student for the changing and diverse world. This process however is unattainable without values, which are possessed by students individually, and are used to interact with society. Developing values is imperative for gifted students, and they are trained to do this through an increase of social competences, proper curriculum and teacher guidance. VaKE is a didactical approach, which combines knowledge acquisition with values education through the use of dilemmas.